The meaning of Palestinians sacrifice in the lyric of the song “We Will Not Go Down”: Semiotic analysis of Ferdinand de Saussure - Zakiyah, Amanda Arichah (Maliki Interdisciplinary Journal, 2024)
Music is the science or art of arranging tones or sounds in order, combination, and temporal relationships to produce sound compositions that have unity and continuity. In making music, a composer must master the basic knowledge of tone and rhythm. In addition, the composer must also be adept at choosing words that will be poured into songs. Usually, a song is made based on an event or experience, either happy or sad. This discussion focuses on the sad events experienced by the Palestinians in Michael Heart’s "We Will Not Go Down.". To obtain information related to the meaning of the Palestinian people’s sacrifice in the song, researchers used qualitative methods and Ferdinand De Saussure’s semiotic theory. Ferdinand De Saussure’s semiotic concept is based on the object of study in the form of a sign.